The influence of Blockchain technology on reducing cybersecurity risks in financial transactions of commercial banks - Ali Eyadat, Ahmad; Alamaren, Amro S.; Almomani, Siwar Lutfi (Frontiers in Blockchain, 2025)
This quantitative research investigates the influence of Blockchain technology on reducing cybersecurity risks in financial transactions of commercial banks in Jordan. It aims to determine the extent to which Blockchain technology can reduce cyber risks faced by commercial banks in Jordan. A structured questionnaire consisting of 12 items was designed based on the research question about how Blockchain technology affects and contributes to cybersecurity to check the main objective of this study. This questionnaire has been handed out to respondents who are currently employed in Jordanian commercial banks. Here, stratified sampling was used to ensure that the data collected were representative of different segments of banks, providing a more accurate analysis of the views of the various members of the banking industry. The study used TAM to determine and check the scope of factors that influence the acceptance and adoption of Blockchain technology among banking professionals. Results have been positive, showing that Blockchain technology does cut or minimize the risk of cybersecurity on financial transactions in these institutions. The findings of this study thus warrant that Jordanian commercial banks should, with immediate effect, follow the integration of Blockchain solutions into their respective systems to enhance and ensure cybersecurity. Through this, the banks are able to protect their operations and encourage the clients to trust the digital banking sector.